Management of pediatric ankle fractures: comparison of biodegradable PLGA implants with traditional metal screws - Nudelman, Hermann; Lőrincz, Aba; Lamberti, Anna Gabriella; Varga, Marcell; Kassai, Tamás; Józsa, Gergő (Frontiers in Pediatrics, 2024)
Introduction The relevance of biodegradable implants has gained more importance in modern clinical practice. The study aimed to evaluate the effects and outcomes of ankle fracture treatment with absorbable implants compared to metal screws. These implants are made from poly l-lactic-co-glycolic acid (PLGA), however, there are several other materials available on the market. Methods In a retrospective review, a total of 128 patients were under observation, with distal tibial fracture types ranging from Salter-Harris II-IV. In the absorbable group, patients were treated with the implants (n = 76). The metal group included patients treated with titanium or steel screws (n = 52). The extremities were placed in a cast for six weeks after surgery and were utilized for another 6–8 weeks. Patients were followed up for 12–30 months and were evaluated accordingly. The authors examined several aspects such as age, gender, open or closed repair, mechanism of injury, length of hospitalization, type of fracture, time of recovery, and complications. Results There were no statistically significant differences between the groups regarding demographic qualities, such as age, type of fracture, side of injury, and length of cast application (p > 0.05 in all cases). Out of 76 patients in the PLGA group, only two presented with complications, so reoperation took place. The rest healed without complications or refractures. Two of those treated with metal screws (n = 52) had minor, and four had major complications with reoperation. Discussion In pediatric cases, PLGA implants may present excellent results for treating ankle fractures. They do not disturb the growth plate and do not require reoperation. For this reason, they reduce the burden on the patient and the healthcare provider while simultaneously decreasing the risk of complications, such as infections or problems due to general anesthesia.